Poverty, Income Distribution, and Economic Policy in the Philippines - Gerson, Philip (IMF Working Papers; Working Paper ;, 1998)
Income distribution in the Philippines is highly uneven, and poverty rates are higher than in other ASEAN countries. In addition, although the poverty rate has declined over time, the rate of decline has been lower than in other countries, and income inequality has been persistent. These facts are due to historically slow economic growth, owing in part to poor policies, as well as to past failures to reduce structural impediments to a more equal distribution of income. Despite reforms in recent years, it will likely take some time to erase the effects of past policies.